The Influence of Causal Thinking with Scaffolding Type 2A and 2B on Optics Problem-Solving Ability (Department of Physics, Faculty of Mathematics and Natural Sciences, 2018)
The effectiveness of learning is affected by the assistance stages (scaffolding) provided. For example, the scaffolding of type 2a and type 2b supports the causal-thinking approach in learning. The type 2a informs the causal model, number of causes and effect, while 2b informs its argument sample. This research aimed to identify the effect of causal thinking process (CTP) with scaffolding type 2a and 2b on optics problem-solving ability (PSA) of students. The type of the research was quasi-experiment with the non-equivalent-group design. Data were obtained with PSA-test and analyzed with the two-tail test with separated variance formula at significance degree of 5% to determine the effect of each type of the CTP on the PSA, also to determine its difference. The results showed that tcount for each of the first two t-tests were greater than ttable, but tcount for the third one was smaller than its ttable. This research concluded that the implementation of the CTP with the scaffolding of type-2a and 2b were effective to improve the student’s PSA. However, the improvements were not different.Efektivitas pembelajaran dipengaruhi bantuan tahapan (scaffolding) yang diberikan. Dengan pendekatan berpikir kausalitik ini, diperkenalkan scaffolding tipe-2a dan tipe-2b. Kedua scaffolding ini menginformasikan model kausal serta jumlah Cause dan Effect tetapi pada tipe-2b ditambah contoh argumentasinya. Penelitian ini bertujuan mengidentifikasi pengaruh proses-berpikir-kausalitik (PBK) ber-scaffolding tipe-2a dan tipe-2b terhadap kemampuan-pemecahan-masalah (KPM) optik siswa. Jenis penelitian kuasi-eksperimen dengan desain non-equivalent-group. Data diambil menggunakan alat tes-KPM dan dianalisis dengan uji-t dua pihak menggunakan rumus separated varians pada signifikansi 5% untuk mengetahui pengaruh PBK tipe-2a dan 2b terhadap KPM, serta perbedaan kedua pengaruh tersebut. Hasil menunjukkan nilai thitung untuk dua uji-t pertama lebih besar dari tTable terkait tetapi nilai thitung untuk uji ketiga adalah lebih kecil dari tTable-nya. Simpulan penelitian implementasi PBK ber-scaffolding tipe-2a dan 2b masing-masing berpengaruh terhadap peningkatan KPM siswa tetapi kedua pengaruh tersebut tidak berbeda.